Cover Image, Volume 37, Issue 9. (September 2017) - Katsube, Motoki; Yamada, Shigehito; Miyazaki, Reina; Yamaguchi, Yutaka; Makishima, Haruyuki; Takakuwa, Tetsuya; Yamamoto, Akira; Fujii, Yosuke; Morimoto, Naoki; Ito, Tsuyoshi; Imai, Hirohiko; Suzuki, Shigehiko
Abstract : Nasal profiles reconstructed using magnetic resonance imaging data of human embryos and fetuses in the prenatal period. From Katsube et al., Prenatal Diagnosis37 : 907–915, DOI:10.1002/pd.5106 .